1991
DOI: 10.1152/ajpheart.1991.260.3.h752
|View full text |Cite
|
Sign up to set email alerts
|

Carotid sinus baroreceptor reflex control of venular pressure-diameter relations in rat intestine

Abstract: We tested the hypothesis that the venules of the small intestinal muscle are responsible for decreases in vascular capacitance during bilateral carotid artery occlusion. We measured microvascular venular pressure and diameter relations in 135 vessels during both control and baroreflexive conditions (bilateral carotid occlusion). Microvascular pressure was measured using a servo-null pressure system, and diameters were obtained from a video-monitoring system with a total magnification of X1,000. First-, second-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…It is highly compliant, contains about 30% of total circulating blood, and is subject to reflex control of intraluminal volume (15,32). Our attention was therefore directed to whether there was a difference in reactivity and compliance of the splanchnic (mesenteric) veins from RB and virgin rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly compliant, contains about 30% of total circulating blood, and is subject to reflex control of intraluminal volume (15,32). Our attention was therefore directed to whether there was a difference in reactivity and compliance of the splanchnic (mesenteric) veins from RB and virgin rats.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the necessarily limited scope of this admit tedly pragmatic study, we did not evaluate the immuno suppressive response to a range of anesthetic doses, but chose instead conventional doses used in a number of lab oratories, including those which study the microcircula tion intravitally [1, [18][19][20][21], One can always argue that a lower dose would have had a lesser effect, but in each case we carefully monitored our rats and had chosen the mini mum doses to produce humane levels of anesthesia, i.e.. those that suppressed the pain response without inducing hypotension nor respiratory suppression. In most cases, this involved the administration of a defined dose of drug.…”
Section: Discussionmentioning
confidence: 99%
“…Thiopental (100 mg/kg) was administered intravenously by slow bolus injection via the tail vein. This dose was previously used by Hum et al [18] and Haase and Shonkas [19] in their intravital microscopic studies of the rat brain and intestine. Wc avoided intraperitoneal injection to eliminate the potential for local (topical) effects on the mesentery.…”
Section: Treatment Protocolsmentioning
confidence: 99%
“…They inferred that this mechanism might cause a 30% to 40% change in cardiac output per 25-mmHg change in sinus pressure. Among their subsequent studies [11,17,29], Shoukas and his colleagues demonstrated that the pressure-diameter relationships of rat mesenteric first-, second-, and fourth-order venules shifted toward the pressure axis when the carotid arteries were occluded [17]. [Venular diameter is determined solely by its transmural pressure; it is independent of the velocity of flow (A.A. Shoukas, personal communication).]…”
Section: Normal Physiologic Mechanismsmentioning
confidence: 99%